A highly flexible and sensitive piezoresistive sensor based on MXene with greatly changed interlayer distances. Issue 1 (December 2017) - Ma, Yanan; Liu, Nishuang; Li, Luying; Hu, Xiaokang; Zou, Zhengguang; Wang, Jianbo; Luo, Shijun; Gao, Yihua
Abstract Since the successful synthesis of the first MXenes, application developments of this new family of two-dimensional materials on energy storage, electromagnetic interference shielding, transparent conductive electrodes and field-effect transistors, and other applications have been widely reported. However, no one has found or used the basic characteristics of greatly changed interlayer distances of MXene under an external pressure for a real application. Here we report a highly flexible and sensitive piezoresistive sensor based on this essential characteristics. An in situ transmission electron microscopy study directly illustrates the characteristics of greatly changed interlayer distances under an external pressure, supplying the basic working mechanism for the piezoresistive sensor. The resultant device also shows high sensitivity (Gauge Factor ~ 180.1), fast response (<30 ms) and extraordinarily reversible compressibility. The MXene-based piezoresistive sensor can detect human being's subtle bending-release activities and other weak pressure. MXenes are a family of layered materials which show promise for a variety of (opto-)electronic applications. Here, the authors leverage the variations of the interlayer distance in Ti3 C2 under external pressure to devise a piezoresistive sensor.